Urgensi Labelisasi Halal Daging Impor di Indonesia - Khoiriyah, Khoiriyah (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2021)
This article discusses the import of meat which has become a polemic, because the halal label was lost or not included in the Indonesian Minister of Trade Regulation, this research is a form of analysis of how important and urgent the halal label is on imported meat in Indonesia as a Muslim-majority country. This study uses a content analysis method with a qualitative approach. Based on the facts and analysis carried out, the researchers concluded that: The halal label on meat imported to Indonesia is very important, because the majority of Indonesian people are Muslims who rely on halal and haram food for a product when consuming it. Halal labels are not enough to ensure a product is always halal. So, in this case, especially meat products, the meat production process must be considered regularly and the role of the state is needed to periodically check the meat production process so that it can always be ensured that it is halal